2020
DOI: 10.3390/ijms21186644
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanisms by Which Vitamin D Prevents Insulin Resistance and Associated Disorders

Abstract: Numerous studies have shown that vitamin D deficiency is very common in modern societies and is perceived as an important risk factor in the development of insulin resistance and related diseases such as obesity and type 2 diabetes (T2DM). While it is generally accepted that vitamin D is a regulator of bone homeostasis, its ability to counteract insulin resistance is subject to debate. The goal of this communication is to review the molecular mechanism by which vitamin D reduces insulin resistance and related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 299 publications
(394 reference statements)
4
80
1
7
Order By: Relevance
“…The VDRE sequence is highly variable. The role of this complex is remodeling of chromatin and communication with RNA polymerase II to the transcription start site [ 22 , 23 , 27 , 41 , 43 ].…”
Section: Briefly About Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The VDRE sequence is highly variable. The role of this complex is remodeling of chromatin and communication with RNA polymerase II to the transcription start site [ 22 , 23 , 27 , 41 , 43 ].…”
Section: Briefly About Vitamin Dmentioning
confidence: 99%
“…Recent findings reveal that the molecular mechanism of vitamin D involves insulin secretion and signaling, and thereby supports glycemic control and insulin sensitivity [ 21 ]. In light of the complex functions of vitamin D, covering the regulation of gene expression engaged in proliferation, differentiation, autophagy, apoptosis, epithelial–mesenchymal transition (EMT), modulation of cell–microenvironment interactions, antioxidants, enzymes, angiogenesis, and inflammation, it is suggested that vitamin D deficiency may be a key player of T2DM-cancer association, since it contributes to the exacerbation of disorders accompanying diabetes [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently a consensus on the optimal vitamin D concentration or supplementation for deficiency does not exist [258,259]. The Scandinavian Nutrition Societies, the European Society for clinical and Economic Aspect of Osteoporosis and Osteoarthritis, the North American Institute of Medicine, the German Osteology governing body (DVO) and D-A-CH nutrition societies have agreed that a circulating level of 25(OH)D should not be lower than 50 nmol/L, and below 25-30 nmol/L indicates deficiency [246,260,261].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Studies investigating the efficacy of vitamin D supplementation have demonstrated significant effects on circulating vitamin D, total cholesterol, glycated hemoglobin (HbA1c), low density lipoproteins (LDL), homeostatic model assessment (HOMA-IR), and triglyceride levels, all leading to improving metabolic pathways and insulin resistance [246,262]. It is suggested that vitamin D supplementation in individuals with T2D may need to be significantly higher to achieve an adequate 25(OH)D levels due to the increased amount of adipose tissue and lower base vitamin D levels [258,263].…”
Section: Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation